The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/hec.1555
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lone motherhood on the smoking behavior of young adults

Abstract: We provide evidence that living with an unmarried mother during childhood raises smoking propensities for young adults in Germany. Copyright © 2010 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Recent studies using a similar estimation method are Ermisch and Francesconi (), Siedler (), Francesconi et al . (), Currie et al . () and Anderson et al .…”
Section: Effect Of Family Non‐intactness During Childhood On Adult CImentioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies using a similar estimation method are Ermisch and Francesconi (), Siedler (), Francesconi et al . (), Currie et al . () and Anderson et al .…”
Section: Effect Of Family Non‐intactness During Childhood On Adult CImentioning
confidence: 96%
“…An extensive body of research across a range of disciplines has identified childhood family structure as a key determinant of children's later life socio-economic outcomes, emphasizing that children who grow up in a non-intact family tend to perform less well in school and to gain lower educational qualifications than children from intact families (Case et al, 2001;Ermisch et al, 2004;Gruber, 2004), are more likely to leave home when young and to become sexually active or pregnant at an early age (McLanahan and Sandefur, 1994) and tend to report higher levels of smoking (Francesconi et al, 2010a). However, one aspect of childhood family structure has remained largely neglected in the literature: its influence on children's later life civic engagement.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several studies have also found early‐life conditions as a relevant determinant of health inequalities with a large range of social background factors, such as low parental socioeconomic status (e.g. Currie and Stabile, , Case et al , , Lindeboom et al , , Rosa‐Dias, , Jusot et al , , Trannoy et al , ); family issues, such as living in a single parent family or experiencing marital discord (Case and Katz, , Francesconi et al , ); parents’ health status (Trannoy et al , ); or health‐risk lifestyles (Anda et al , , Göhlmann et al , , Jusot et al , ). However, the importance of lifestyles in the magnitude of health inequalities is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Marmot et al , , Case et al , , Trannoy et al , ). Moreover, parents’ lifestyles and social status as well as early‐life conditions would also be associated with health‐related behaviours in later life such as smoking (Rosa‐Dias, ; Göhlmann et al , ; Francesconi et al , ), alcohol consumption (Anda et al , ); obesity (Power et al , ; Laitinen et al , ; von Hinke Kessler Scholder, ). In the sense that early‐life conditions such as parents’ lifestyles, socioeconomic status as well as childhood economic conditions are individual characteristics from childhood, one would agree that they are causal factors of adult education and lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, smoking initiation has been found to be related to mother's education and parents' smoking behaviour (Rosa-Dias, 2009;Göhlmann et al, 2010;Power et al, 2005). Living with a lone mother during childhood seems to be also associated with greater risks of smoking among young adults (Francesconi et al, 2010). Alcohol consumption among young adults has also been related to father's alcohol consumption (Zhang et al, 1999) and alcoholism in adulthood is also more frequent among individuals who have known adverse childhood circumstances and whose parents were alcohol addicts (Anda et al, 2002).…”
Section: Estimation Strategymentioning
confidence: 99%